The Effect of Job Promotion on Work Motivation and Work Engagement - Mahardianyah, Mahardianyah; Mauludin, Hanif (Journal of Industrial Engineering & Management Research, 2025)
Promotion is a form of organizational appreciation for employees who have achievements and potential, and is believed to be able to increase motivation and work involvement. However, there have not been many studies that comprehensively examine the relationship between job promotion, job motivation, and work engagement in one complete model. This study aims to analyze the effect of job promotion on employee work motivation and work engagement. The research method used is a quantitative approach with the Partial Least Square–Structural Equation Modeling (PLS-SEM) analysis technique using SmartPLS software. The sample in this study consists of employees of a government agency who have received a promotion to a position within a certain period of time. The results of the study show that promotion has a positive and significant effect on work motivation, and work motivation significantly affects work involvement. In addition, work motivation has been shown to significantly mediate the relationship between job promotion and job engagement. These findings make a theoretical contribution in strengthening the literature on organizational behavior and provide practical implications for human resource management, especially in designing promotional policies capable of increasing work engagement through increased employee motivation.